Pengaruh Ukuran Perusahaan, ROA (Return On Asset), DER (Debt To Equity Ratio), Dan TATO (Total Asset Turn Over) Terhadap Perataan Laba - Sri Rahayu; Elisa Elsera; Eduard Hotman Purba (UNIVERSITAS RAHARJA, 2015)
This study aims to analyze the influence of the firm size, ROA (Return on Assets), DER (Debt To Equity Ratio), and Total Asset Turnover for income smoothing, either partially or simultaneously. Variabels used in the study as independent variabels are firm size, ROA (Return on Assets), DER (Debt To Equity Ratio), and Total Asset Turnover. While the dependent variabel is income smoothing. The population in this study are all companies manufacturing food and beverage field are listed in the Indonesia Stock Exchange year of 2008-2011, as many as 14 companies, with a total sample of 8 companies that passed the stage purposive sampling. Analysis techniques that will be used this research is logistic regression to obtain an overall picture of the relationship between one variabel with another variabel. Processing is done by using logistic regression with SPSS version 19. Independent variabels used in this study are firm size, ROA (Return on Assets), DER (Debt To Equity Ratio), and Total Asset Turnover and income smoothing as the dependent variabel. The data analysis used in this study were descriptive statistics, assessing model fit,-2loglikehood, Cox's and Snell's R square nagekerke's R square, Hosmer and Lemeshow's goodness-of-fit test, and 2 x 2 classification tables. The test results in this study show that the simultaneous testing and retesting or separate company size (X1) significantly influence income smoothing (Y), while ROA (Return on Assets) (X2), DER (Debt To Equity Ratio) (X3) , and Total Asset Turnover (X4) does not have a significant impact on income smoothing (Y) as the dependent variabel.